Early Results of Congenital Clubfoot Treatment With Ponseti Method - Zehir, Sinan; Sipahioğlu, Serkan; Altay, Mehmet Akif; Ertürk, Cemil; Bilge, Ali; Işıkan, Uğur Erdem (Fırat University, 2012)
Objective: The purpose of this study is to evaluate early results of ponseti method for the treatment of congenital club foot. Materials and Methods: A total of 27 patients' (38 clubfeet,17 boys, 10 girls; mean age 12 day) were treated by Ponseti method during the periot of 2009 to 2010 years. Eleven patients had bilateral and 16 pateints had unilateral clubfoot. Patients,which were treated by another medical center or had any concomitant illness ,were not included into this study. Some patients were excluded from this study, because they left the treatment or they did not use their splint. Mean follow up period was 14 months (12-17 months). We have performed percutenous achilles tenotomy in all patients. Results: Clinically we achieved exellent results in the patients whose method was performed properly.The radiological evaluation of these patients were also satisfactory. Poor compliance with the splint and or improper method of surgery were the main problems in these patients. Conclusion: Correct applying the Ponseti method, carefully following up the patients with frequent periods, education problems of patients' parents and orthotists, lack of understanding and poor compliance of patients' parents can all affect a successful outcome.

Amaç: Ponseti yöntemi ile tedavi edilen doğuştan çarpık ayaklı (DÇA) olguların erken dönem sonuçlarını değerlendirmek. Gereç ve Yöntem: Çalışmaya 2009-2010 yıllarında Ponseti yöntemi ile tedavi edilmiş 27 (17 erkek, 10 kız ortalama yaş 12 gün ; dağılım 0- 35 gün) hastanın 38 ayağı alındı. Hastalardan 11'inde çift 16'sında tek taraflı deformite vardı. Tek taraflı olguların 9'unda sol 7'sinde sağ ayak etkilenmişti. Başka bir merkezde Doğuştan çarpık ayak(DÇA) tedavi gören, eşlik eden hastalıkları olan olgular çalışmaya dahil edilmedi. DÇA tanısı ile alçılamaya başlanıp devam edilemeyen yada ortez kullanmayan olgular çalışma dışında tutuldu. Ortalama takip süresi 14ay(12-17 ay) idi. Hastaların tamamına perkütan aşil tenotomisi uygulandı. Bulgular: Bir yıllık takip sonrasında yöntemin tam olarak uygulandığı ve çalışmaya dahil edilen 27 olgunun tamamında klinik olarak düzelme elde edildi. Bu olguların radyolojik değerlendirmesinde de normal sınırlarda değerler elde edilmiştir. Uygulamadaki en önemli sorun otez kullanımına uyum sağlanması ve uygun ortez yapımının sağlanamaması olduğu gözlenmiştir. Sonuç: Ponseti yöntemi ile DÇA tedavisinde başarılı bir sonuç için yöntemin kurallarına uygun şekilde titizlikle uygulanması, olguların sık ve yakından takibi ve ailelerin eğitiminin yanında ortotist eğitimininde önemli olduğu düşünülmektedir.
Ponseti Yöntemi ile Tedavi Edilen Doğuştan Çarpık Ayaklı Olguların Erken Dönem Sonuçları